Territorial cohesion and air transport in Spain - Martín Osante, José Manuel (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The purpose of this work is to study the legal regime of the so-called public service obligations provided for in Regulation (EC) n. 1008/2008 and its application on Spanish air routes. These obligations constitute measures that limit or exclude the free access of airlines to the EU market, in order to prevent certain routes from being neglected due to lack of economic profitability, and to guarantee territorial cohesion and mobility. Specifically, this article examines the scope of Spanish and European legal provisions on the protection of territorial cohesion, the EU legal regime of public service obligations and describes the application in Spain of these obligations.
Keywords: public service obligations; Regulation 1008/2008; air transport; territorial cohesion; regional development